2007
DOI: 10.3354/dao076169
|View full text |Cite
|
Sign up to set email alerts
|

First report of erythrocytic inclusion body syndrome (EIBS) in chinook salmon Oncorhynchus tshawytscha in Alaska, USA

Abstract: Juvenile seawater-reared chinook salmon Oncorhynchus tshawytscha at a hatchery on Baranoff Island, Alaska, USA, sustained chronic mortality associated with anemia and mixed infections by various obligate and opportunistic pathogens including a cytoplasmic erythrocytic virus resembling the agent of erythrocytic inclusion body syndrome (EIBS). This is the first case report of EIBS in Alaska and is a range extension of the disease. KEY WORDS: Erythrocytic inclusion body syndrome · EIBS · Anemia · Chinook salmon R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Similarly, in a previous study of PRV, the blood, spleen, and kidney had the highest viral RNA loads of the 11 tissues tested in HSMI-affected Atlantic salmon [29]. It is generally understood that erythrocytes are the target cells of both PRV species (causative agents of EIBS and/or HSMI), because they form inclusion bodies in these cells [2, 7, 8, 12, 14, 30, 31]. An analysis of the incidence of immature erythrocytes and inclusion bodies led to the hypothesis that immature erythrocytes are initially infected with the causative agent of EIBS [32, 33].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, in a previous study of PRV, the blood, spleen, and kidney had the highest viral RNA loads of the 11 tissues tested in HSMI-affected Atlantic salmon [29]. It is generally understood that erythrocytes are the target cells of both PRV species (causative agents of EIBS and/or HSMI), because they form inclusion bodies in these cells [2, 7, 8, 12, 14, 30, 31]. An analysis of the incidence of immature erythrocytes and inclusion bodies led to the hypothesis that immature erythrocytes are initially infected with the causative agent of EIBS [32, 33].…”
Section: Discussionmentioning
confidence: 76%
“…The virions are also occasionally free in the cytoplasm of erythrocytes or combined within large cytoplasmic vacuoles [10]. The preliminary characterization of this virus with electron microscopy revealed similar characteristics to those of a member of the family Togaviridae [11], but the isolation of the virus in a fish cell line has been unsuccessful, preventing its further characterization [12]. …”
Section: Introductionmentioning
confidence: 99%
“…PRV replicates preferentially in red blood cells, forming intraerythrocytic inclusion bodies (IBs; Finstad et al, 2014;Haatveit et al, 2016;Wessel, Olsen, Rimstad, & Dahle, 2015) that are morphologically reminiscent of the inclusion bodies associated with erythrocytic inclusion body syndrome (EIBS; Leek, 1987;Piacentini, Rohovec, & Fryer, 1989). However, EIBS is associated with anaemia and is typically found in association with other diseases (Meyers, 2007;Piacentini et al, 1989). No changes in haematocrit values were observed in challenge studies of Atlantic and sockeye salmon conducted using PRV from western North American (Garver, Johnson et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of reports of viral inclusions in salmonid erythrocytes that have been collectively termed EIBS [ 26 ]. No specific viruses have been recognized as causative agents and erythrocytic inclusions assumed to be of viral origin have been observed in salmonid species in both the Atlantic and Pacific, including Atlantic salmon, rainbow trout ( O. mykiss ), Chinook salmon ( O. tshawythscha ) and Coho salmon ( O. kisutch ) [ 21 , 23 , 55 ]. The PRV particles and inclusions described in our study have a striking resemblance to several of the previously reported viral inclusions described as EIBS [ 21 - 25 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…No specific viruses have been recognized as causative agents and erythrocytic inclusions assumed to be of viral origin have been observed in salmonid species in both the Atlantic and Pacific, including Atlantic salmon, rainbow trout ( O. mykiss ), Chinook salmon ( O. tshawythscha ) and Coho salmon ( O. kisutch ) [ 21 , 23 , 55 ]. The PRV particles and inclusions described in our study have a striking resemblance to several of the previously reported viral inclusions described as EIBS [ 21 - 25 , 55 ]. Pinacyanol chloride staining has previously been used in identification of EIBS [ 26 , 56 ], and in the present study we observed stained inclusions using this techniques.…”
Section: Discussionmentioning
confidence: 99%